Analysis of correlation between ICI and desired carrier power in OFDM systems over frequency-selective ricean fading channels under the influence of doppler spread. - Yen, Rainfield Y. (Journal of Applied Science and Engineering)
For data detection in orthogonal frequency division multiplexing (OFDM) systems over mobile wireless channels, the inter-carrier interference (ICI) term arising from Doppler spread is correlated with the desired carrier term. In this paper, we carry out detailed analysis on the power correlation between the ICI and the desired signal term. Explicit closed form expression for the covariance function of the ICI and the desired carrier power is derived for frequency selective Ricean fading channels. This expression shows that, in the normal Doppler spread range corresponding to practical vehicular speeds, the ICI power is appreciably correlated with the desired carrier power.